2007
DOI: 10.1007/s10689-007-9125-0
|View full text |Cite
|
Sign up to set email alerts
|

The Teesside Cancer Family History Service: change management and innovation at cancer network level

Abstract: The Teesside project took the underlying principle of the Kenilworth model--that people with a family history of cancer should be 'triaged' and signposted to appropriate clinical services--and applied it to a whole clinical cancer network in which inequity was the major driver for change. Unlike the Kenilworth model, the Department of Health/Macmillan Cancer Support-funded pilot project in Teesside embedded genetic risk assessment at secondary care level. The project took a 'bottom up' approach that engaged a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Most articles focused on only one of these aspects, mainly genetic counseling, and were therefore excluded. The present systematic review consists of 117 records (Brain et al, 2000, 2002; Gray et al, 2000; Harper et al, 2000; Massie et al, 2000; Pichert and Stahel, 2000; Bach et al, 2001; Bickerstaff et al, 2001; Donnai and Elles, 2001; Ekstein and Katzenstein, 2001; Heath et al, 2001; Shepherd et al, 2001, 2003, 2014; Wonderling et al, 2001; Charron et al, 2002; Hartenbach et al, 2002; Lee et al, 2002; Lena-Russo et al, 2002; The Genetic Services Plan for Wisconsin, 2002; Anton-Culver et al, 2003; Barlow-Stewart et al, 2003; Campbell et al, 2003; Fry et al, 2003; Gason et al, 2003, 2005; Hopwood et al, 2003; Menkiszak et al, 2003; Rowland et al, 2003; Salbert, 2003; Comeau et al, 2004; Henriksson et al, 2004; Holloway et al, 2004; Kornreich et al, 2004; Basran et al, 2005; Calzolari and Baroncini, 2005; Epplein et al, 2005; Gozdzik et al, 2005; Hanley, 2005; Henry et al, 2005; Byck et al, 2006; Foretova et al, 2006; Gronwald et al, 2006; Mackay and Taylor, 2006; Puryear et al, 2006; Reis et al, 2006; Ricker et al, 2006; Therrell et al, 2006; Westwood et al, 2006; Windmill and Windmill, 2006; Young et al, 2006; Allen et al, 2007; Bennett et al, 2007, 2010; Berkenstadt et al, 2007; Brennan et al, 2007; Drury et al, 2007; Eeles et al, 2007; Gulzar et al, 2007; Mak et al, 2007; Morad et al, 2007; Southern et al, 2007; Srinivasa et al, 2007; Tozer and Lugton, 2007; Williams et al, 2007; Coffey et al, 2008; Eisinger, 2008; Kaye, 2008; Washing...…”
Section: Resultsmentioning
confidence: 99%
“…Most articles focused on only one of these aspects, mainly genetic counseling, and were therefore excluded. The present systematic review consists of 117 records (Brain et al, 2000, 2002; Gray et al, 2000; Harper et al, 2000; Massie et al, 2000; Pichert and Stahel, 2000; Bach et al, 2001; Bickerstaff et al, 2001; Donnai and Elles, 2001; Ekstein and Katzenstein, 2001; Heath et al, 2001; Shepherd et al, 2001, 2003, 2014; Wonderling et al, 2001; Charron et al, 2002; Hartenbach et al, 2002; Lee et al, 2002; Lena-Russo et al, 2002; The Genetic Services Plan for Wisconsin, 2002; Anton-Culver et al, 2003; Barlow-Stewart et al, 2003; Campbell et al, 2003; Fry et al, 2003; Gason et al, 2003, 2005; Hopwood et al, 2003; Menkiszak et al, 2003; Rowland et al, 2003; Salbert, 2003; Comeau et al, 2004; Henriksson et al, 2004; Holloway et al, 2004; Kornreich et al, 2004; Basran et al, 2005; Calzolari and Baroncini, 2005; Epplein et al, 2005; Gozdzik et al, 2005; Hanley, 2005; Henry et al, 2005; Byck et al, 2006; Foretova et al, 2006; Gronwald et al, 2006; Mackay and Taylor, 2006; Puryear et al, 2006; Reis et al, 2006; Ricker et al, 2006; Therrell et al, 2006; Westwood et al, 2006; Windmill and Windmill, 2006; Young et al, 2006; Allen et al, 2007; Bennett et al, 2007, 2010; Berkenstadt et al, 2007; Brennan et al, 2007; Drury et al, 2007; Eeles et al, 2007; Gulzar et al, 2007; Mak et al, 2007; Morad et al, 2007; Southern et al, 2007; Srinivasa et al, 2007; Tozer and Lugton, 2007; Williams et al, 2007; Coffey et al, 2008; Eisinger, 2008; Kaye, 2008; Washing...…”
Section: Resultsmentioning
confidence: 99%
“…Less than a third of the 258 articles citing Klein and Sorra's [1] work discuss implementation climate, and many that do refer to the construct do so only in passing. Second, researchers have sometimes treated implementation climate as synonymous with related, yet distinct constructs such as receptive organizational context [10,11], supportive organizational context [12], and organizational culture [13]. Third, notwithstanding the widespread appeal of Klein and Sorra's [1] theory, the construct of implementation climate has been assessed empirically in only six studies [14-19], one of which was qualitative assessment [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the early years of this study, criteria for enrolment in the programme were less strictly applied than currently. We and others have found that investment in checking, extending and validating reported family histories substantially alters the distribution of assessed risk and allows better targeting of screening 8 23 24. Applying that principle, as we have done since the late 1990s, should increase the cancer incidence rate among those enrolled in surveillance.…”
Section: Discussionmentioning
confidence: 86%